A knowledge-based web platform for collaborative physical system modeling and simulation - Zhang, Yanshan (2013)
A web platform, called Proteus (http://www.visualphysics.net/pweb), has been developed by a team in Nanyang Technological University. This platform is designed for education and academic research, and is free to use. It provides a place where students, educators, and academic researchers can easily create and share their computer models of physical systems described using Modelica, a non-proprietary, object-oriented, equation-based language for physical system modeling. It comes with a web-based, graphical modeling, and simulation tool called ProteusGWT (http://www.visualphysics.net/ProteusGWT). ProteusGWT is web-based and uses an intuitive, graphical component-oriented approach to the modeling of physical systems spanning multiple domains including systems containing mechanical, hydraulic, thermal, control, electrical, electronic, electric power, or process-oriented subcomponents. It synthesizes state-of-the-art web technologies (e.g., HTML5, GWT, and cloud computing), computational methods for physical systems modeling, and simulation to create a computing environment that is widely deployable and scalable. Google Web Toolkit (GWT) is a development toolkit from Google for building and optimizing complex web-based applications. It allows developers to create and maintain complex JavaScript applications in Java language. Proteus allows anyone with a computer or browser-enabled device to be able to use it. Hence, anyone can contribute their computer models of physical systems to this platform. As this platform grows, it could turn out to be an online interactive repository for all kinds of physical system models, for example, a student may examine complete computer models of a motorcycle, a refrigerator, a burglar alarm, or robot arm and learn about how they work. He or she could run simulations, modify the models, or create new designs and share with others. There is nothing quite like this currently on the Internet.